2016
DOI: 10.1038/srep33116
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin carboxyl-terminal hydrolase-L5 promotes TGFβ-1 signaling by de-ubiquitinating and stabilizing Smad2/Smad3 in pulmonary fibrosis

Abstract: Transforming growth factor β-1 (TGFβ-1)-induced phosphorylation of transcription factors Smad2 and Smad3 plays a crucial role in the pathogenesis of idiopathic pulmonary fibrosis (IPF). However, the molecular regulation of Smad2/Smad3 proteins stability remains a mystery. Here, we show that ubiquitin carboxyl-terminal hydrolase-L5 (UCHL5 or UCH37) de-ubiquitinates both Smad2 and Smad3, up-regulates their stability, and promotes TGFβ-1-induced expression of profibrotic proteins, such as fibronectin (FN) and α-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Uch37 has been implicated in DNA replication and cell cycle [141], TGF-β signaling [142145], WNT signaling via Tcf7 [146], longevity [147], cell migration and invasion [148], and the reversal of ubiquitination of proteasome subunits [138]. It is difficult to resolve common themes from the physiological studies reported to date.…”
Section: Physiological Functionmentioning
confidence: 99%
“…Uch37 has been implicated in DNA replication and cell cycle [141], TGF-β signaling [142145], WNT signaling via Tcf7 [146], longevity [147], cell migration and invasion [148], and the reversal of ubiquitination of proteasome subunits [138]. It is difficult to resolve common themes from the physiological studies reported to date.…”
Section: Physiological Functionmentioning
confidence: 99%
“…UCHL5 encodes ubiquitin carboxyl-terminal hydrolase-L5 a deubiquitinating enzyme that stabilizes several Smad proteins and TGFBR1, key components of the TGF-beta1 signalling pathway [31,32] .…”
Section: Exemplar Regionsmentioning
confidence: 99%
“…Con, control; Dia, diabetes; Dia+4-PBA, diabetes group treated with 4-PBA; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; SEM, standard error of the mean F I G U R E 5 Expression of ERAD components in the cerebral cortex of rats. 32 This is the first study to show the alteration in the expression of the UCHL5 protein in the brain of diabetic rats, and its role remains to be explored. Expression values were represented as fold change over control on an arbitrary scale after normalization with β-actin.…”
Section: Discussionmentioning
confidence: 92%